2015
DOI: 10.1111/dme.12694
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic vs basal bolus insulin regimen in Type 2 diabetes: a systematic review and meta‐analysis of randomized controlled trials

Abstract: Biphasic and basal bolus regimens were equally effective in reducing HbA1c in insulin naïve patients with Type 2 diabetes and both regimens are equally effective for initiating insulin in Type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
27
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 39 publications
0
27
0
1
Order By: Relevance
“…Finally, in a subgroup analysis in insulin-naïve patients, premixed regimen had no difference with basal-bolus regimens (-0.15 %; -0.52 to 0.22) [11].…”
mentioning
confidence: 87%
See 4 more Smart Citations
“…Finally, in a subgroup analysis in insulin-naïve patients, premixed regimen had no difference with basal-bolus regimens (-0.15 %; -0.52 to 0.22) [11].…”
mentioning
confidence: 87%
“…Similarly, the recently published GALAPA-GOS study demonstrated that in insulin-naive patients, premixed insulin once or twice daily reduced HbA 1c by a further 0.16 % (confidence interval 0.04 to 0.27) compared with insulin glargine with or without insulin glulisine [10]. Finally, in a subgroup analysis in insulin-naïve patients, premixed regimen had no difference with basal-bolus regimens (-0.15 %; -0.52 to 0.22) [11].For patients already on basal insulin, results from the LanScape study suggested that basal-plus regimens (glargine plus insulin glulisine once daily) are non-inferior to premixed insulin (biphasic insulin aspart 30 twice daily) in reducing HbA 1c [12]. However, a recent meta-analysis by Wang et al concluded that basal-bolus regimens have superior glycemic efficacy to premix insulin in non-insulinnaïve patients (-0.22 %; -0.42 to -0.02) [11].…”
mentioning
confidence: 93%
See 3 more Smart Citations